Micro Evidence on International Patenting - Per Botolf Maurseth; Roger Svensson (Research Institute of Industrial Economics (IFN), 2012)
Globalization, high growth rates in high-tech industries, growing emerging markets and harmonization of patent institutions across countries have stimulated patenting in foreign markets. We use a simple model of international patenting, where the decision to patent in a foreign country depends on country characteristics and the quality of the patented invention. With access to a detailed database on individual patents owned by Swedish small firms and inventors, we are able to estimate some of these relationships and test their validity. Our results indicate that the propensity to apply for international patent protection increases with indicators of the quality of the invention and indicators of technological rivalry and market size in the host market.
Keywords: O33; O34; 330; International patenting; Host country characteristics; Patent value